Welded steel beam with novel cross-section and web openings subject to concentrated flange loading. (April 2020) - Russell, Matthew J.; Lim, James B.P.; Roy, Krishanu; Clifton, G. Charles; Ingham, Jason M.
Highlights: A new generation steel beam with a novel dog-bone shaped cross-section, referred to as the Dinobeam is developed. Ten experimental concentrated flange loading tests are described that cover typical loading conditions. Test results showed that the web to flange welds have sufficient strength and ductility to resist a tearing failure in bearing. Finite element (FE) models were then developed and validated against the experimental results. The validated FE models were used to conduct an extensive parametric study to investigate the effect of different parameters. Abstract: This paper describes the development of a steel beam with a novel dog-bone shaped cross-section, referred to as the Dinobeam. The Dinobeam is intended for use as a secondary floor beam in high-rise construction, capable of spanning distances greater than 12 m. The cross-section comprises triangular shaped flanges, which are press-braked to an overlapping fit and then continuously welded to a web plate at each flange-to-web junction, i.e. with two welds per flange. The primary advantage of the Dinobeam cross-section is the fact that its closed hollow flanges give the cross-section increased resistance to lateral torsional buckling compared to the typical I-cross section. In this paper, ten experimental concentrated flange loading tests are described that cover typical loading conditions, the tests include Dinobeams both with and without circular web openings. The experimental test results show that the flange-to-web PJP welds have sufficient strength and ductility to resist a tearing failure when subject to bearing. Finite element models were then developed and validated against the experimental results. The validated finite element models were used to conduct an extensive parametric study comprising 108 finite element models, to investigate the effect of thicknesses, bearing length, and hole diameter to web height ratios.